A cultural theory of international relations - Lebow, Richard Ned (Cambridge University Press, 2008)
In this volume, Richard Ned Lebow introduces his own constructivist theory of political order and international relations based on theories of motives and identity formation drawn from the ancient Greeks. His theory stresses the human need for self-esteem, and shows how it influences political behavior at every level of social aggregation. Lebow develops ideal-type worlds associated with four motives: appetite, spirit, reason and fear, and demonstrates how each generates a different logic concerning cooperation, conflict and risk-taking. Expanding and documenting the utility of his theory in a series of historical case studies, ranging from classical Greece to the war in Iraq, he presents a novel explanation for the rise of the state and the causes of war, and offers a reformulation of prospect theory. This is a novel theory of politics by one of the world's leading scholars of international relations.